Analysis of aerobic and anaerobic endurance levels in junior soccer players in various field positions - Suhadak, Ahmad; Syafii, Imam; Nanda, Fitri Agung (Research and Social Study Institute, 2024)
In football, the energy system used is aerobic endurance and anaerobic endurance. So every football player needs to have the quality of endurance in facing every match. The aim of this research is to determine the ability of aerobic endurance and the ability of anaerobic endurance. The subjects of this research were 20 junior football players aged 14 years. The research method in this research is quantitative with a descriptive approach. The instruments used in the research were the Running Anaerobic Sprint Test (RAST) for collecting data on anaerobic endurance and the Multistage Fitness Test (MFT) for aerobic endurance. The percentage results of aerobic endurance were 3 people in the very poor category, 6 people in the poor category, 8 people in the sufficient category, and 3 people in the good category. Meanwhile, regarding anaerobic endurance, 8 people were in a good category, 6 people were in the sufficient category, and 3 people were in the very poor category. From the description results for the anaerobic endurance variable, the mean is 5.99, the standard deviation is 0.39. Meanwhile, from the results of the description for the aerobic endurance variable, the mean was 39.90, standard deviation of 4.73. Based on the results of the research conducted, it can be concluded that there is an influence of aerobic and anaerobic training on endurance in junior football athletes in the city of Kediri. Even though it has an influence on the durability of this research, it has several limitations, namely limited subjects and age categories.